DATABASE MONITORING AND OPTIMIZATION TOOLS (Multidisciplinary Journal of Science and Technology, 2025)
This article discusses the role of database monitoring and optimization tools in improving the efficiency of information systems. Methods for identifying and optimizing database problems such as overloads, slow queries, and inefficient resource usage using monitoring tools are scientifically analyzed. Special attention is also paid to ensuring system stability through indexing, query optimization, resource management, and backup mechanisms. The results of the study show that the effective use of monitoring and optimization tools is important in ensuring the speed, reliability, and uninterrupted operation of the database.